Techniques for Reducing Iron (Fe) Content in Groundwater: an Article Review - Yazid, Edy Agustian; Wafi, Abdul; Saraswati, Arina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Iron is a chemical element that is found in almost every place on earth, including in well water or groundwater. Iron can be suspended in water with organic substances or inorganic solids in the form of ferrous cations (Fe2+) and ferries (Fe3+). The presence of iron that exceeds the threshold can cause detrimental effects such as corrosion of the piping, the color of the water turns brown, smells bad, and can cause health problems. The iron content in groundwater can be reduced so that it can be used as water that is fit for consumption or use in everyday life. This study aims to determine several types of techniques used to reduce iron in groundwater or well water through literature studies. Techniques covered include filtration, aeration, adsorption, coagulation, electrocoagulation, and cascade aerators. The results showed that the greatest reduction in efficiency was found in the combination type of adsorption technique and filtration technique by more than 99.1%, then followed by the electrocoagulation technique of Â 99.74%. From all the techniques studied in this study, it can be concluded that all techniques can reduce iron levels in which the combination of adsorption and filtration techniques is the most effective.Keywords: Technique, reduction, iron content, groundwater